Bad country - Brinker, Chris; Dillon, Matt; Dafoe, Willem; McDonough, Neal (Culver City, California : Sony Pictures Home Entertainment, 2014)
A contract killer acts as an informant for a local detective and sets out for revenge after his family is executed by a syndicate boss.
Originally released as a motion picture in 2014.
Dolby digital 5.1, wide screen 1.78:1.
Features: deleted scenes; Taking down an empire : on the set.
Matt Dillon, Willem Dafoe, Neal McDonough, Amy Smart, Tom Berenger.
MPAA rating: R.
In English or French with optional English or French subtitles.
Keywords: Murder for hire -- Drama; Undercover operations -- Drama; Murder -- Drama; Revenge -- Drama; Crime films; Action and adventure films; Fiction films; Video recordings for the hearing impaired; Thriller films; Feature films